THE MEANING OF ONE-WAY COMMUNICATION IN MUDABBIR FILM BY DIRECTOR ARFEDDIN HAMAS: SEMIOTIC OF ROMAN JAKOBSON - Choirunisa, Wanda; Rohanda (English Literature Department, Faculty of Economics, Law, and Humanities, 2024)
In literary work, there is communication between characters that contains meaning in it. From one of these types of communication there is a type of one-way communication. In this study, the author examined the film Mudabbir which aired on the Gontor TV youtube channel by director Arfeddin Hamas. The theory used by the author in researching this research is Roman Jakobson's semiotics which consists of six aspects, namely sender, receiver, context, code, message, and contact. The method used in this research is qualitative by using the free listening technique. The result of this research shows the meaning behind one-way communication contained in Mudabbir film with Roman Jakobson's semiotic theory includes direction, good advice from the board to its members.